2016
DOI: 10.1148/radiol.2016151472
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Supine Breast MR Imaging to Quantify Tumor Deformation and Detection of Residual Breast Cancer: Preliminary Results

Abstract: Purpose To use intraoperative supine magnetic resonance (MR) imaging to quantify breast tumor deformation and displacement secondary to the change in patient positioning from imaging (prone) to surgery (supine) and to evaluate residual tumor immediately after breast-conserving surgery (BCS). Materials and Methods Fifteen women gave informed written consent to participate in this prospective HIPAA-compliant, institutional review board–approved study between April 2012 and November 2014. Twelve patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…No difference in tumor volume according to posture change was found. This differs from a study by Gombos et al 15 which observed an average change of 23.8% in the measured tumor volume in 12 patients. This is likely due to the fact that this study only had six cases that underwent both pre-and post-surgical supine MRI.…”
Section: Discussioncontrasting
confidence: 99%
“…No difference in tumor volume according to posture change was found. This differs from a study by Gombos et al 15 which observed an average change of 23.8% in the measured tumor volume in 12 patients. This is likely due to the fact that this study only had six cases that underwent both pre-and post-surgical supine MRI.…”
Section: Discussioncontrasting
confidence: 99%
“…These images are made with the breast in a different position to that on the operating table, making extrapolation of the exact position and growth pattern of the DCIS difficult during surgery. Gombos and colleagues showed considerable deformity of the breast and change in tumour position between MRI in the supine and prone positions. Sakakibara and co‐workers reported a lower rate of positive resection margins after MRI in the supine position than in the prone position in patients with DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as intraoperative information nowadays is important during CAI, preoperative images could be updated with the intraoperative data (surface) acquired by the ConoProbe. Gombos et al have recently described their experience with a supine intraoperative MR imaging protocol to evaluate tumor deformation. For the same procedure, Ungi et al propose an US‐based framework relying on a tracked stylus for acquiring the necessary surface points.…”
Section: Discussionmentioning
confidence: 99%